Academic freedom, tenure, and student evaluations of faculty: A response to Haskell and his critics. - Cisneros-Cohernour, Edith J. (Education Policy Analysis Archives, 2005)
I comment on the strengths and limitations of Haskell's article and provide a critical review of his arguments about the negative impact of SEF on tenure and other administrative decisions. I object to the limited evidence supporting the claim that the use of student evaluations per se challenges academic freedom.